Hubungan Pengetahuan, Sikap, dan Identifikasi Kandungan Boraks pada Jajanan Kantin Universitas Muhammadiyah Bengkulu - Evan Nasrullah, Muhammad (Avicenna: Jurnal Ilmiah, 2025)
Background: Food safety is to prevent food and beverages from being contaminated by foreign substances, whether physical, biological, or chemical, so as to reduce the potential for illness due to food hazards. Purpose of the study To determine attitudes and knowledge towards borax content in canteen snacks at the University of Muhammadiyah Bengkulu. Method: The research method used is a descriptive observational laboratory method. Results: From the results obtained, the Pearson correlation value between the borax content variable and knowledge is 0.134 because the correlation value is in the range of 0.00-0.199, the relationship between the two variables is very low. It is known that the Pearson correlation value between the borax content variable and knowledge is 0.071 because the correlation value is in the range of 0.00-0.199, the relationship between the two variables is very low. Conclusion: there is no relationship between knowledge and borax content in canteen snacks, with a very low relationship category. There is no relationship between attitudes and borax content in canteen snacks, with a very low relationship category. It is recommended that snack sellers in the canteens of campus 1 and campus 4 of Muhammadiyah University of Bengkulu be aware of the dangers of borax content in food and prioritize consumer health. Keywords: Food Safety, Knowledge, Attitude, Snacks